Microalgal bioengineering: A futuristic tool for carbon capture - Adamu Yunusa Ugya; Yangyang Sheng; Hui Chen; Qiang Wang (Results in Engineering)
Microalgae is a sustainable tool for carbon capture and bioprospecting due to its unique characteristics, but its scale-up application has been hindered by different challenges. This study alluded to the potential for overcoming existing barriers and easing the application of microalgae-based solutions in carbon capture technologies. The mechanisms by which different bioengineering techniques enhance the photosynthetic efficiency, carbon fixation pathways, and stress tolerance in microalgae, leading to carbon capture, were also explored. These bioengineering techniques were deciphered towards scale-up cultivation of microalgal resources and application in carbon capture. The success of scale-up applications was linked to the implementation of metabolic and genetic engineering strategies. These strategies tend to enhance the economic and environmental feasibility of microalgae-based carbon capture technologies. The engineering of microalgae stress responsive mechanisms was shown to improve biomass productivity and resilience of microalgae. The pathway towards the eradication of issues related to the technical feasibility of microalgae scale-up application in carbon capture was identified. The study buttressed the role of policy and regulatory frameworks in enhancing the feasibility of microalgae usage as a tool in scale-up carbon capture. But to ascertain a scale-up application of microalgae-based technology for carbon capture, research direction should focus on the use of bioengineering techniques to ease the integration of microalgae systems into industrial processes.